Hadrontherapy for Thymic Epithelial Tumors: Implementation in Clinical Practice - Loap, Pierre; Vitolo, Viviana; Barcellini, Amelia; De Marzi, Ludovic; Mirandola, Alfredo; Fiore, Maria Rosaria; Vischioni, Barbara; Jereczek-Fossa, Barbara Alicja; Girard, Nicolas; Kirova, Youlia; Orlandi, Ester (Frontiers in Oncology, 2021)
Radiation therapy is part of recommendations in the adjuvant settings for advanced stage or as exclusive treatment in unresectable thymic epithelial tumors (TETs). However, first-generation techniques delivered substantial radiation doses to critical organs at risk (OARs), such as the heart or the lungs, resulting in noticeable radiation-induced toxicity. Treatment techniques have significantly evolved for TET irradiation, and modern techniques efficiently spare normal surrounding tissues without negative impact on tumor coverage and consequently local control or patient survival. Considering its dosimetric advantages, hadrontherapy (which includes proton therapy and carbon ion therapy) has proved to be worthwhile for TET irradiation in particular for challenging clinical situations such as cardiac tumoral involvement. However, clinical experience for hadrontherapy is still limited and mainly relies on small-size proton therapy studies. This critical review aims to analyze the current status of hadrontherapy for TET irradiation to implement it at a larger scale.